Sistem Informasi Kehadiran Karyawan Berbasis Android Menggunakan Metode Geofencing Pada Pt. Gemilang Anugrah Permata - Zeka Prahudi Vianto; Eka Rini Yulia (Computer Science (CO-SCIENCE), 2022)
The development of technology is so fast that it becomes very necessary in everyday life in order to simplify and optimize human performance in order to get information quickly, effectively and accurately. The use of information technology is a strong factor that greatly influences the development of a company. Currently, its development has begun to move towards mobile phones (mobile / smartphone). Currently, companies can take advantage of the development of information technology in almost all areas of the company's operations. PT. Gemilang Anugrah Permata is a company engaged in IT solutions and security systems, has dozens of employees assigned to go directly to the field to install CCTV and solve problems. Often in practice employees do permission to come directly to the client's location, resulting in the admin needing to re-enter the employee's presence. In that case the accuracy of attendance becomes irrelevant because sometimes employees do not come according to the specified working hours when they come to the client. So it is necessary to develop a web and android-based information system with the geofencing method so that employees can take attendance while at the client according to a predetermined point and the attendance data becomes accurate.